Anatomy of the honey bee - Snodgrass, R. E. (Robert E.), 1875-1962 (Comstock Pub. Associates, 1984)
First published in 1956, this classic work on the anatomy of honey bee by R. (Robert) E. Snodgrass is acclaimed as much for the author's remarkably detailed line drawings of the various body parts and organs of his subject as for his authoritative knowledge of entomology and the engaging prose style with which he conveys it. This book should be in the library of every student of the honey bee and bee behavior-beekeepers (both amateur and professional) as well as scientists.